A high-fructose diet leads to osteoporosis by suppressing the expression of Thrb and facilitating the accumulation of cholesterol - Jun Chen; Xinquan Jiang (Cell Death Discovery)
Abstract Osteoporosis is classified as a metabolic syndrome, and the consumption of fructose has been linked to various metabolic diseases. However, the specific effects and underlying mechanisms of fructose on bone health remain inadequately understood. In this study, we demonstrate that fructose intake can exacerbate bone loss in murine models by facilitating the accumulation of cholesterol within the bones. We identify Thyroid Hormone Receptor Beta (Thrb) and Protein Kinase C Zeta (Prkcz) as potential therapeutic targets for the treatment of osteoporosis. Mice subjected to a high-fructose diet exhibited a reduction in bone density and a decrease in the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) compared to those on a standard diet. Fructose treatment was found to decrease Thrb expression while increasing Prkcz expression, leading to cholesterol accumulation and hindering the osteogenic differentiation of BMSCs. Furthermore, our findings indicate that the activation of Thrb and the inhibition of Prkcz significantly ameliorate bone loss in mice. This study elucidates the molecular mechanisms by which fructose influences osteogenesis through the Thrb/Prkcz/cholesterol accumulation pathway in the context of osteoporosis, thereby highlighting the therapeutic potential of Thrb and Prkcz as targets for osteoporosis treatment.